2010
DOI: 10.1111/j.1600-0501.2010.01981.x
|View full text |Cite|
|
Sign up to set email alerts
|

Maxillary sinus floor elevation with bovine bone mineral combined with either autogenous bone or autogenous stem cells: a prospective randomized clinical trial

Abstract: Mesenchymal stem cells seeded on BioOss(®) particles can induce the formation of a sufficient volume of new bone to enable the reliable placement of implants within a time frame comparable with that of applying either solely autogenous bone or a mixture of autogenous bone and BioOss(®). This technique could be an alternative to using autografts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
185
0
9

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(202 citation statements)
references
References 23 publications
(48 reference statements)
8
185
0
9
Order By: Relevance
“…To reconstruct bony defects, for example, adding mononuclear stem cells derived from a bone marrow aspirate to Bio-Oss 1 has been shown to result in bone forming kinetics comparable to autogenous bone alone, after a healing period of 3-4 months 23,25 . These mononuclear stem cells can differentiate to osteoblasts if they are added to a bony matrix.…”
Section: Discussionmentioning
confidence: 99%
“…To reconstruct bony defects, for example, adding mononuclear stem cells derived from a bone marrow aspirate to Bio-Oss 1 has been shown to result in bone forming kinetics comparable to autogenous bone alone, after a healing period of 3-4 months 23,25 . These mononuclear stem cells can differentiate to osteoblasts if they are added to a bony matrix.…”
Section: Discussionmentioning
confidence: 99%
“…They found that HGF-loaded scaffolds promoted mineralisation, angiogenesis, new bone formation and β-TCP absorption [20]. Sauerbier et al [21] and Rickert et al [22] performed randomised controlled clinical trials to investigate formation of new bone in patients with severe atrophy of the maxillary sinus. Patients obtained an augmentation of the sinus from bovine bone material either with BMAC or autologous bone.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the vast majority of articles published recently in the literature have focused on the use of autologous stem cells in atrophic mandibles to induce and enhance new bone formation to allow implant placement. For instance, Rickert et al (2011), Katagiri et al (2016), Kawai et al (2015), and Yamada et al (2013) have observed and documented the safe use of mesenchymal stem cell (MSC) bone marrow (BM)-derived bone augmentation for dental implants in patients affected by severe alveolar bone atrophy. All of these authors indicated that this minimally invasive bone regeneration technique was a useful and novel option in dental implant treatment of severe bone atrophy, showing good results through MSCs' great osteogenic potential, together with poor donor site morbidity and few inflammatory signs.…”
Section: Introductionmentioning
confidence: 99%
“…MSCs have the ability to self-renew and present a multilineage potential (Kan et al, 2005). Their plasticity makes them a promising resource for research in cellular therapy of tissue defects, and several authors have demonstrated how autologous stem cells aspirated from BM can enhance bone healing in in vitro and in vivo studies (Kan et al, 2005;Rickert et al, 2011;Watson et al, 2014;Katagiri et al, 2013;Osugi et al, 2012;Inukai et al, 2013;Kawai et al, 2015;Katagiri et al, 2016). In this regard, osteoinductive growth factors such as bone morphogenic protein (BMP)-2 have been already used with osteoconductive materials to promote bone regeneration (Herford and Boyne, 2008).…”
Section: Introductionmentioning
confidence: 99%